2017
DOI: 10.1292/jvms.17-0204
|View full text |Cite
|
Sign up to set email alerts
|

Systemic mycobacteriosis caused by ‘<i>Mycobacterium avium</i> subspecies <i>hominissuis</i>’ in a 14-month-old Japanese black beef steer

Abstract: A 14-month-old Japanese black beef steer presented with severe chronic diarrhea and emaciation and was euthanized. Postmortem examination showed thickened and corrugated intestinal mucosa and enlarged granulomatous mesenteric lymph nodes with caseating necrosis. Numerous epithelioid cells and multinucleated giant cells infiltrated in the lamina propria and the submucosal tissue of the intestines. These cells were also observed in the systemic organs. Many acid-fast bacilli were detected in the cytoplasm of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…An experimental infection of goats with MAH performed by Schinköthe et al demonstrated two different courses of disease with highly heterogenic lesions, systemic spread in goats with severe clinical disease and the development of granulomas of all stages in the surviving goats ( 5 ). Recently in Asia, a Japanese black beef steer was discovered to have MAH granulomas in the systemic organs, indicating that MAH can cause systemic mycobacteriosis in cattle ( 6 ). Especially in developed countries, MAH is frequently linked to human mycobacteriosis ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…An experimental infection of goats with MAH performed by Schinköthe et al demonstrated two different courses of disease with highly heterogenic lesions, systemic spread in goats with severe clinical disease and the development of granulomas of all stages in the surviving goats ( 5 ). Recently in Asia, a Japanese black beef steer was discovered to have MAH granulomas in the systemic organs, indicating that MAH can cause systemic mycobacteriosis in cattle ( 6 ). Especially in developed countries, MAH is frequently linked to human mycobacteriosis ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It provides comfort to animals and doesn't have a negative influence on the production of animals. The structure of wood and chemical profile stops the growth of some harmful pathogens, thus the method of production and wood species [59][60][61] has a clear effect on the antimicrobial behavior. After use, this bedding material can either be recycled or biotransformed to be used for other purposes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recycling processes maintain the safety of bedding material without harmful effects on animals [41]. Sawdust may be contaminated by some microbes which can cause infection not only in animals but their zoonotic potential can reach up to humans too [39] (Sampimon et al 2006; Komatsu et al 2017). It doesn't mean that wood bedding is less safe in such scenario [42] because similar organisms have been isolated from other beddings too [43].…”
Section: Sawdustmentioning
confidence: 99%
“…M. avium isolates of human origin have been found to closely resemble those of pig origin [68], suggesting the existence of epidemiological links between infections in pigs and infections in humans, or of infections from common sources [68]. Pigs commonly become infected from sources in the external environment, such as litter, feed, water or soil, following contamination with the faeces of wild birds or small land mammals [6]; infection typically occurs through the alimentary route [42,69].…”
Section: Pathogenesis and Immunology Of Infection The Exact Pathogenesis Of Mac Infections And Their Virulence Factorsmentioning
confidence: 99%